Niveles de abonadura de biopalma más sulfato de magnesio en cultivo establecido de palma africana (Elaeis guineensis jacq.) etapa de producción. - Pazmiño Zambrano, Pablo Enrique (2013)
We evaluated "abonadura levels of magnesium sulfate Biopalma more established growing palm (Elaeis guineensis Jacq.) Production stage. The research was conducted in Puerto Quito Canton, Pichincha Province, Salazar River sector, Zone 18, Fundo Guanábano farm, owned by Mr. Jose Vega, 163 km Calacalí Independence, at an altitude of 120 meters. 5 treatments were employed with the application of Triple 15 (Control) 5 kg / plant; Biopalma 4 kg / plant; Biopalma 3 kg + 1 kg of magnesium sulfate / plant; Biopalma + 2 kg 2 kg of magnesium sulfate / plant; and Biopalma 1 kg + 3 kg of magnesium sulfate / plant and the overall objective was: To evaluate different levels of Biopalma abonadura over magnesium sulphate established culture of African palm (Elaeis guineensisJacq.)productionstage. The results for the variables increase in the diameter of the base of the stipe (m); increased height (m); emission of clusters for four months, the plant and better production per hectare by the end of the experiment was to Treatment T4 (Biopalma 2 kg + 2 kg of magnesium sulfate / plant), with 0.052 m, 0.054 m, 4.094 clusters; 3.447 kg / plant and 492.9 kg / ha., in that order. The cost / benefit ratio unfavorable because research into the third year of production is still poor for being still young plantations. The results allow us to accept the hypotheses "The study of the combination of manure and chemical fertilizer in oil palm plantations established in the production influences". "The use of 2 kg of Biopalma + 2 kg of magnesium sulfate improves yield per hectare and profitability in the production of palm oil." Keywords: Abonadura, Biopalma, Production, Oil Palm.